2017
DOI: 10.1177/1526602816687086
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Thoracic Endovascular Aortic Repair on Pulsatile Circumferential and Longitudinal Strain in Patients With Aneurysm

Abstract: TEVAR was associated with an increase of pulsatile longitudinal strains (in the arch) and circumferential strains (at the celiac trunk) in unstented aortic segments. These observations suggest increased pulsatile wall stress after TEVAR in segments adjacent to the device, which may contribute to the understanding of stent-graft-related complications such as retrograde dissection, aneurysm formation, and rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…7 Animal models have linked compliance mismatch between prosthetic endovascular grafts and the native descending aorta to postprocedure complications such as dissection, aneurysmal dilatation, and rupture distal to the repair. 6,23,24 Nauta et al 25 assessed the impact of thoracic endovascular aortic repair on aortic strain using cardiac gated computed tomography and found that implantation of the prosthetic stent graft was associated with increased pulsatile longitudinal strain and circumferential strain proximal and distal to stented aortic segments. The authors hypothesised that this may contribute to stent graft related complications such as retrograde dissection, aneurysm formation, and rupture.…”
Section: Discussionmentioning
confidence: 99%
“…7 Animal models have linked compliance mismatch between prosthetic endovascular grafts and the native descending aorta to postprocedure complications such as dissection, aneurysmal dilatation, and rupture distal to the repair. 6,23,24 Nauta et al 25 assessed the impact of thoracic endovascular aortic repair on aortic strain using cardiac gated computed tomography and found that implantation of the prosthetic stent graft was associated with increased pulsatile longitudinal strain and circumferential strain proximal and distal to stented aortic segments. The authors hypothesised that this may contribute to stent graft related complications such as retrograde dissection, aneurysm formation, and rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous aortic DENSE study from healthy adult volunteers, 12 this range would be consistent with aortic strains from the majority of healthy adults over 35 years of age. However, for future applications in the assessment of aortopathies such as aneurysms and dissections, aortic DENSE must quantify focal and/or generalized stiffening that can yield circumferential strains as low as 1%–5% 29–31 . Future tests with improvement in the strength and variability of the phantoms may allow testing over a broader range of strains, including focused evaluations of stiff phantoms with strains <2% to mimic aortopathies and more compliant phantoms with strains ≥10% to mimic young aortas.…”
Section: Discussionmentioning
confidence: 99%
“…Strain causes alterations that can result in mechanical stress, causing dSINE which leads to pseudoaneurysm. 8,20,21 This is seen especially at the transition zones between the rigid stent graft and the fragile aortic wall. The dissection membrane of acute dissections is approximately 15 times more prone to dSINE development compared with that of chronic dissections, and might therefore be at particular risk.…”
Section: Discussionmentioning
confidence: 99%